Perbandingan Hukum Perlindungan Investor Antara Indonesia dan Negara ASEAN dalam Menghadapi Investasi Ilegal - Elawati, Tuti; Mbunai, La Ode; Panca Prana Mustaqim Sinaga, Muhammad; Suparman, Yusuf (Universitas Sains Indonesia Publishing, 2025)
The increasing prevalence of fraudulent investment schemes across Southeast Asia reflects weaknesses in investor protection frameworks and the ineffectiveness of regulatory oversight over illegal investment activities. This study aims to analyze and compare the legal frameworks for investor protection in Indonesia and selected ASEAN countries, particularly Malaysia and Singapore, in addressing fraudulent investment practices. The research employs a normative juridical approach using comparative legal analysis. The findings indicate that Indonesia has established a legal basis for investor protection through Law No. 8 of 1995 on Capital Markets and supervision by the Financial Services Authority (OJK). However, its implementation and enforcement still face various challenges, such as low investment literacy and weak sanctions against offenders. In contrast, Malaysia and Singapore have adopted stricter regulations through integrated financial supervision and the use of early detection technologies to monitor illegal investment activities. The comparison highlights the need for strengthening supervisory mechanisms, enhancing legal and financial literacy among the public, and promoting regulatory harmonization among ASEAN countries to build an effective and responsive investor protection system in the digital investment era.